ONLINE BIOMEDICAL RESOURCES: A PAKISTANI PERSPECTIVE - Ullah, Midrar; Khan, Muhammad Najeeb (Pakistan Armed Forces Medical Journal, 2006)
Medical literature has been particularly well organized for over a century in comparison with some other disciplines, medical literature is relatively easy to use. There are well-established medical publishers who enjoy credibility and good reputation due to quality of their books and journals. Indexing and abstracting services are functioning since the 1870s. These have been quick to adopt modern technologies. Now in an age of amazing advances in computer technology, the handling of medical information sources is well under control and techniques for bibliographic organization hold great promise [1].